Axisymmetric Arc Sliding Method of Basal Heave Stability Analysis for Braced Circular Excavations - Mingju Zhang (Symmetry, 2018)
On the basis of the circular arc sliding model of the limit equilibrium method, an axisymmetric arc sliding method (AASM) is proposed to analyze the basal heave stability of braced circular excavations. The proposed method considers the stiffness of the enclosure structure and spatial effects. The AASM was applied to check basal heave stability in a design example and provided results that were more reasonable than those obtained using other methods. The radii effects in theory and numerical simulation, and the enclosure structure stiffness effects on the basal heave stability safety factor were discussed. Additionally, the effects of the embedded depth on the basal heave stability of a braced circular excavation were analyzed. The safety factor of basal heave stability for a braced circular excavation will be larger when calculated with the AASM than when calculated with the circular arc sliding method, and the optimized embedded depth of the enclosure structure may therefore be reduced by 4∼5 m to lower the cost of the enclosure structure.